2022
DOI: 10.3390/ijms23063028
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism and Aging of Hematopoietic Stem and Progenitor Cells

Abstract: Comprehensive proteomics studies of human hematopoietic stem and progenitor cells (HSPC) have revealed that aging of the HSPC compartment is characterized by elevated glycolysis. This is in addition to deregulations found in murine transcriptomics studies, such as an increased differentiation bias towards the myeloid lineage, alterations in DNA repair, and a decrease in lymphoid development. The increase in glycolytic enzyme activity is caused by the expansion of a more glycolytic HSPC subset. We therefore dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Senescence can also lead to cellular metabolic changes with deleterious consequences. For example, human hematopoietic stem and progenitor cells as well as human fibroblasts have been shown to display increased glucose uptake and glycolysis, and lipid accumulation (Gorgoulis et al, 2019;Poisa-Beiro et al, 2022). This alteration in lipid handling is detrimental in that it accumulates within lysosomes as indigestible lipofuscin, impairing lysosomal function and autophagic capabilities.…”
Section: Detrimental Effectsmentioning
confidence: 99%
“…Senescence can also lead to cellular metabolic changes with deleterious consequences. For example, human hematopoietic stem and progenitor cells as well as human fibroblasts have been shown to display increased glucose uptake and glycolysis, and lipid accumulation (Gorgoulis et al, 2019;Poisa-Beiro et al, 2022). This alteration in lipid handling is detrimental in that it accumulates within lysosomes as indigestible lipofuscin, impairing lysosomal function and autophagic capabilities.…”
Section: Detrimental Effectsmentioning
confidence: 99%
“…Several glycolytic enzymes are upregulated in aging HSPCs [ 189 ], possibly contributing to CHIP formation. CHIP therapy focuses on preventing the onset and progression of hematological malignancies.…”
Section: Hsc Agingmentioning
confidence: 99%
“…The research showed that the structure of MLN2238 is different from bortezomib (15). MLN2238 (ixazomib) has been given great promise because of the proven clinical effects of bortezomib which was another proteasome inhibitor (16,17). Moreover, the disassociation half-life of ixazomib was six-fold faster than bortezomib which made ixazomib fast dissociate from red blood cells and rapidly entered into the tumor cells (18).…”
Section: Introductionmentioning
confidence: 99%